Bridging the gap in public health education in India: the need of the hour - Marinaik, Shrinivasa Basavegowdana Doddi; Jayanandan, Rajesh; ., Nagendra (International Journal of Research in Medical Sciences, 2017)
Background:Lack of proper communication skills among budding doctors is considered to be a major gap existing between teaching and practice of public health in various parts of India. Therefore a competency based teaching curriculum is needed to sharpen these skills necessary for bridging this gap and achieving a successful community based medical education. Methods:This cross-sectional study was conducted among a group of 28 students from a batch of 133 students in their fourth semester of second year undergraduate medical education, who attended their posting in the department of community medicine at JSS medical college (JSS University) in Mysore, for a period of one month during May 2014. A new educational intervention namely student’s short seminar was included in addition to their routine community medicine teaching curriculum. At the end of the postings a feedback regarding the intervention was collected from the students using a pretested structured questionnaire. Results:Questions related to the intervention were rated by the students in a six point Likert scale. The median total score was 15.0 (12-17). Among 28 students majority 16 (57.1%) of them had graded it as good while 11 (39.3%) had graded it as fair and 1 (3.6%) of them had graded it as poor based on the median total score. Conclusion:Community based medical education can fulfil its purpose when it can advocate not only the cognitive domain (Knowledge) but also the affective domain (Attitudes) and psychomotor domain (Skills) of the learning process. Hence it is the foremost duty of the faculties in the department of community medicine in medical colleges to inculcate interest towards public health by introducing innovative and interactive teaching and learning interventions.